Fractionated low-dose radiation exposure potentiates proliferation of implanted tumor cells - Gerashchenko, B.I.; Ryabchenko, N.M.; Glavin, O.A.; Rodionova, N.K.; Makovetska, L.I.; Ganzha, O.B.; Druzhyna, M.O.; Mikhailenko, V.M. (Experimental Oncology, 2013)
Aim: The purpose of this study is to test whether whole-body fractionated exposure of tumor-free animals to low doses of low-LET radiation (at the total delivered dose of 1.0 Gy of X-rays) is capable of potentiating growth of subsequently implanted tumor cells. Materials and Methods: Adult male rats were fractionally exposed to low doses of X-rays (10 acute exposures with 0.1 Gy each and with a frequency of 1 exposure per 3 days). The next day after the last irradiation rats were implanted with Guerin carcinoma (GC) cells. On the 12th and 18th days after implantation of GC cells, animals were sacrificed, and the mass of tumors was measured by weighing them, although the kinetics of tumor growth was also examined by daily measurements of the dimensions of tumors. Cytotoxic effects in the bone marrow were assessed flow cytometrically in acridine orange-stained unfractionated bone marrow cells using the ratio of polychromatic erythrocytes (PCE) to normochromatic erythrocytes (NCE). Results: In irradiated rats, tumors grew apparently faster than in unirradiated rats for up to 18 days after implantation of GC cells. On the 18th day after implantation of GC cells the average value of the mass of tumors in irradiated rats was 2.8-fold higher compared with the average value of the mass of tumors in unirradiated rats (p < 0.05). On this day post-implantation, the bone marrow in irradiated animals was 1.8-fold more suppressed (as evidenced by decreased PCE/NCE ratios) than that in animals that were irradiated, but were not implanted with GC cells (p > 0.05), and was 1.4-fold more suppressed than that in animals that were not irradiated, but were implanted with GC cells (p > 0.05). Conclusion: Fractionated irradiation of tumor-free animals with low doses of X-rays potentiates proliferation of subsequently implanted GC cells. This potentiation seems to be associated with radiation-induced impaired hematopoiesis.